Systemic patterns of trabecular bone across the human and chimpanzee skeleton - Tsegai, Zewdi J. (J Anat, 2018)
Aspects of trabecular bone architecture are thought to reflect regional loading of the skeleton, and thus differ between primate taxa with different locomotor and postural modes. However, there are several systemic factors that affect bone structure that could contribute to, or be the primary factor determining, interspecific differences in bone structure. These systemic factors include differences in genetic regulation, sensitivity to loading, hormone levels, diet, and activity levels. Improved understanding of inter‐/intraspecific variability, and variability across the skeleton of an individual, is required to interpret properly potential functional signals present within trabecular structure. Using a whole‐region method of analysis, we investigated trabecular structure throughout the skeleton of humans and chimpanzees. Trabecular bone volume fraction (BV/TV), degree of anisotropy (DA) and trabecular thickness (Tb.Th) were quantified from high resolution micro‐computed tomographic scans of the humeral and femoral head, third metacarpal and third metatarsal head, distal tibia, talus and first thoracic vertebra. We found that BV/TV is, in most anatomical sites, significantly higher in chimpanzees than in humans, suggesting a systemic difference in trabecular structure unrelated to local loading regime. Differences in BV/TV between the forelimb and hindlimb did not clearly reflect differences in locomotor loading in the study taxa. There were no clear systemic differences between the taxa in DA and, as such, this parameter might reflect function and relate to differences in joint loading. This systemic approach reveals both the pattern of variability across the skeleton and between taxa, and helps identify those features of trabecular structure that may relate to joint function.